THE ROLE OF METALINGUISTIC AWARENESS IN LEARNING ENGLISH AS A FOREIGN LANGUAGE: A PSYCHOLINGUISTIC PERSPECTIVE AND ITS IMPLICATIONS FOR CURRICULUM DESIGN - Ithriyah, Siti (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
This research explores the role of metalinguistic awareness in English as a foreign language learning through a psycholinguistics perspective and analyzes its implications for curriculum design. Employing a qualitative approach with library research methods, this study synthesizes academic literature to understand dimensions of metalinguistic awareness including phonological, morphological, syntactic, semantic, pragmatic, and orthographic awareness and their roles in cognitive processes of language learning. Findings indicate that metalinguistic awareness significantly correlates with language skills, particularly reading comprehension, and functions as a strong mediator in achieving linguistic competence. Learners with multilingual backgrounds demonstrate higher performance in metalinguistic awareness compared to monolingual learners. Practical implications suggest the necessity of systematic integration of metalinguistic awareness development activities in curriculum through active learning approaches, utilization of learning technologies, and consideration of multilingual contexts. This research contributes theoretically to enriching applied psycholinguistics literature and offers practical guidance for curriculum developers to design learning programs responsive to learners' cognitive needs by positioning metalinguistic awareness as a core component of English language competence development.